(untitled) (Imaginations: Journal of Cross-Cultural Image Studies, 2014)
Guy Ritchie’s recent blockbuster success with a revisionist Sherlock Holmes is the latest in a series of popular films and fiction to have reinvigorated a nostalgic imaginary of London’s past that places the former capital of the Empire at the crossroads of a persistent Manichean battle between empiricist-driven technological progress and traditions of occult knowledge supposedly submerged in the 17th century yet continuing to trickle into the heart of the Empire from its colonies. By tracing some of these historical layers sedimented into 21st-century popular imaginaries of London’s past, this paper explores the mechanisms of popular culture’s production of nostalgia that mediate public memories and histories and suture them to the imaginary urban geographies that constitute the space of the global city through its metonymic sites and its materialized histories.